(untitled) (Third Sector Social Economic Review, 2025)
In understanding consumer behavior, happiness and satisfaction are increasingly essential elements, especially within the complex dynamics of digitalization in retail sales and consumer habits. This understanding plays a critical role in firms gaining a competitive advantage. This study, using Bandura’s Triadic Determinism Model as a theoretical framework, aims to test the non-linear relationships between consumer satisfaction and immediate and long-term happiness in purchases made on digital platforms, and this interaction according to the levels of purchase intention. In the study conducted with a total of 429 participants, the complex structure and interaction between satisfaction and happiness types were examined through polynomial models. The appropriateness of these non-linear models compared to simple linear models was statistically explained. As a result of the research, the basic hypotheses suggesting that the relationship between consumer satisfaction and both immediate happiness and well-being (long-term happiness) is non-linear were supported. These non-linear interactions were found to vary in different segments defined by consumers’ current levels of satisfaction and happiness. This study is thought to contribute a non-linear solution perspective to existing literature, especially on digital consumers. The findings indicate that the non-linear interaction between consumer satisfaction and happiness necessitates that marketing strategies be more flexible, target-oriented, and segment-specific according to consumers’ different "satisfaction-happiness" profiles. It is suggested that businesses understand these non-linear dynamics and thereby improve the customer experience have the potential to increase customer loyalty in the long term.